QUEING ANALISIS OF AIRCRAFT MOVEMENT AT THE APRON AREA (THE PARKING STAND) IN I GUSTI NGURAH RAI INTERNATIONAL (BALI) - Johar Samosir , Hendro Kuntohadi , Johannes Kurniawan, Sarinah Sihombing , Bonafisius Seno Utomo (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
I Gusti Ngurah Rai International Airport (Bali) is one of the busiest airports in Indonesia which has the potential as a center of tourist destinations for foreign/international tourists. The potential for aircraft movements tend to increase from year to year. One of the facilities that continues to be monitored is the aprons where there are so many parking stands which are the parking lots for aircraft. The results of this study are the arrival of airplanes (?) is 225.6 airplanes / day, or 9.44 airplanes / hour, or 6.35 minutes / airplanes. Then the Utilization (?) of the entire Parking Stand is 30%. The average queue length (Lq) for parking stands is 0 aircraft, and the average queuing time (Wq) is 0 minutes. Then the average number of aircraft in the parking stand system (Ls) is 18.9 aircraft and the average length of time for aircraft in the parking stand system (Ws) is 120 minutes. Keywords: Ngurah Rai International Airport, Parking Stand, Performance